Case report: Urolithiasis, nephrolithiasis and a urinary bladder malformation in a seven-month-old alpaca cria - Schregel, Johannes; Kleinschmidt, Sven; von Altrock, Alexandra; Hoeltig, Doris; Ganter, Martin; Wagener, Matthias G. (Frontiers in Veterinary Science, 2022)
Urolithiasis is a common condition in male small ruminants where predisposing factors have been identified. Occasionally, urolithiasis is diagnosed in South American camelids (SACs). However, nephrolithiasis is rarely diagnosed in ruminants. To our knowledge, this is the first report focusing on a combined appearance of nephrolithiasis and urolithiasis in an alpaca cria. A seven-month-old alpaca cria suffering from impaired urinary flow was presented for examination. On admission, the alpaca had a wet prepuce and showed a standing posture with a wide-based stance. Ultrasonographic examination of the abdomen showed a distended bladder. Clinical chemistry revealed azotemia and hypophosphatemia. After the first examination, repeated urination was observed. Conservative therapy using antibiotics, anti-inflammatory and spasmolytic drugs was started with the suspected diagnosis of urinary calculus. During the first 24 hours, plasma concentrations of creatinine and urea decreased, but increased again during the following days. During the second day after admission, urination was not observed for 16 hours while the concentration of urea and creatinine further increased. Therefore, the animal was euthanized due to financial concerns of the owner. Necropsy revealed that calculi were located in the left kidney as well as in the urethra. In addition, the animal exhibited uroperitoneum. The urinary bladder was intact, moderately distended with urine and showed a malformation, which was covered with a translucent mucosal membrane. Histologic examination revealed that this malformation was a bladder diverticulum. The extent to which the unilateral nephroliths affected the general condition and renal function of the animal is unclear, since the uroliths also cause azotemia, and abdominal pain. Further studies are needed for a better understanding of obstructive urinary disease in SACs.